Послідовна композиція кланів лінійних систем - Zaitsev, D. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
To obtain an additional computational speedup in the course of solution of linear systems, it is proposed to organize a sequential process of composition of their clans. Computational speedup was obtained through the solution of a sequence of clan composition systems with essentially lower dimensions using the graph of system decomposition into clans. A comparative analysis of sequential composition for subgraphs and edge (paired 3) composition was performed. The problem of construction of systems sequence with the lowest dimension was named by a collapse of weighted graph. The upper and lower limits of the collapse width which corresponds to the dimension of systems were estimated. A heuristic algorithm of optimal collapse was constructed and statistically grounded.